Introduction to computer music - Collins, Nick (Nicholas) ([Hoboken] : John Wiley & Sons, 2010)
1. Introduction ##2. Recording ##3. Analysis ##4. Processing #"5. Synthesis ##6. Interaction ##7. Networks ##8. Composition ##9. Modeling ##10. Conclusion
Includes bibliographical references (p. [348]-367) and index.
boek